(untitled) (Research, Society and Development, 2020)
The labial frenulum is an anatomical structure of the upper lip and, when it is positioned close to the gingival margin, it allows the appearance of periodontal problems, generating negative impacts on the patient’s life, such as: aesthetic dissatisfaction, difficulty in lip mobility and oral hygiene . The use of surgical lasers has become widespread in different areas of dentistry and has been highlighted as an alternative for performing frenectomy, due to the fact that, compared to the conventional surgical method, there is less local bleeding, less postoperative pain, no need for suture and presenting rapid local healing. This work reports the case of a pediatric patient who presented fibrous upper labial frenulum, due to trauma in the anterior region of the face, which resulted in the appearance of median diastema between the upper central incisors. Labial frenectomy with diode laser (980nm; 2W; 20pps; 120J; 60Hz, pulsed mode) was performed. Then, photobiomodulation was performed with a low-power diode laser (660nm; 100mW; with 2J of power per point for 20s, punctiform mode) in the region of the incision and the incisive papilla. Thus, this case seeks to illustrate the advantages of laser surgery in relation to other techniques for the removal of the upper labial frenulum.